IRAQ BETWEEN A CULTURE OF CIVIL SOCIETY AND A CULTURE OF VIOLENCE - Al-Saady, Abed Jasem (ALBAHITH ALALAMI, 2007)
The title takes its realistic connotations with its symbols, slogans and historical extensions in Iraq, also, the repercussions of the organic crisis that afflicted it for almost half a century, especially after the abortion of the July 14 Revolution and the spread of the culture of weapons, violence and death that we are living in Iraq nowadays. The topic is suitable for critical analytical studies carried out by specialists in scientific and academic research centers and cultural institutions because they have an important feasibility at the strategic cultural level in Iraq, the Middle East and the world. Research in Iraq has fallen to the extreme and is no longer effective, to the extent that it represents a severe crisis as it lacks freedom and suitable scientific conditions. We try in the following pages to discuss this subject from its political, social and sectarian content, as well as, taking advantage of the Iraqi author references, books "memos" and historical testimonies of some leaders, either because they have begun to feel the responsibility, or because some of them were free to publish his manuscript views after his death! The topic is suitable for critical analytical studies carried out by specialists in scientific and academic research centers and cultural institutions because they have an important feasibility at the strategic cultural level in Iraq and the Middle East and the world. In any case, it remains a positive point of light in self-criticism and experience in rebuilding man and society on new foundations, away from those black claws that have been ravaging Iraq and Iraqis and messing with slogans over time. The researcher in the political topic in Iraq opposes the circumstances of the emergence of the Iraqi state and the establishment of the military "national" formations, which became a permanent base in the conflicts and the acquisition of Iraq which has been used to resolve disputes between military leaders, suppression of movements of protest, insurgency, popular uprisings, the emergence of "coup", blocs and personal relations. Perhaps “Sectarianism” may have had an influential role in containing and controlling the military by involving the country in political conflicts and take control over by the mean of these "national" leaders. The cultural environment of these national officers was limited in their professional positions through the military culture they had acquired in their senior ranks in the Iraqi army, as well as, in the Ottoman Empire or through their social affiliation to feudal and tribal families, which had a special privileges for Britain as one of the first and most important pillars of the occupation and the monarchy in Iraq from its inception until its overthrow in the national revolution of July 1958.